2014
DOI: 10.1016/j.gene.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D pathway genes and HIV-1 disease progression in injection drug users

Abstract: Vitamin-D has pleiotropic effects on calcium and bone metabolism, cellular growth control, cell differentiation and modulation of both innate and acquired immune response. Previous studies revealed the association of vitamin-D receptor gene (VDR) polymorphism with infection diseases including HIV-1 infection. To assess for association between polymorphisms of vitamin-D pathway genes CYP27B1, vitamin-D binding protein (VDBP) and VDR with HIV-1 infection, disease progression to acquired immunodeficiency syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The inference of selection is not surprising, given that earlier studies have also indicated that positive natural selection has operated upon many of these candidate genes to result in a latitudinal cline in human skin pigmentation ( Jablonski and Chaplin 2010 , 2013 ; Beleza et al 2013a ). The skin color genes are well known to influence vitamin D generation by the capacity of melanin to absorb UVB energy, and once vitamin D is produced, its nuclear receptor VDR plays a central role in the signaling of vitamin D to influence a variety of important health-related traits ( Fang et al 2006 ; Uitterlinden et al 2006 ; Azad et al 2012 ; Bikle 2012 ; Disanto et al 2012 ; Jovicic et al 2012 ; Chaplin and Jablonski 2013 ; Christakos et al 2013 ; Mao and Huang 2013 ; Tiosano et al 2013 ; Abd-Allah et al 2014 ; Borella et al 2014 ; Cantorna and Waddell 2014 ; Cutolo et al 2014 ; Laplana et al 2014 ; Liu et al 2014 ; Mann et al 2014 ; Rolf et al 2014 ). Hence, there is also much potential for strong selection at the VDR locus.…”
Section: Discussionmentioning
confidence: 99%
“…The inference of selection is not surprising, given that earlier studies have also indicated that positive natural selection has operated upon many of these candidate genes to result in a latitudinal cline in human skin pigmentation ( Jablonski and Chaplin 2010 , 2013 ; Beleza et al 2013a ). The skin color genes are well known to influence vitamin D generation by the capacity of melanin to absorb UVB energy, and once vitamin D is produced, its nuclear receptor VDR plays a central role in the signaling of vitamin D to influence a variety of important health-related traits ( Fang et al 2006 ; Uitterlinden et al 2006 ; Azad et al 2012 ; Bikle 2012 ; Disanto et al 2012 ; Jovicic et al 2012 ; Chaplin and Jablonski 2013 ; Christakos et al 2013 ; Mao and Huang 2013 ; Tiosano et al 2013 ; Abd-Allah et al 2014 ; Borella et al 2014 ; Cantorna and Waddell 2014 ; Cutolo et al 2014 ; Laplana et al 2014 ; Liu et al 2014 ; Mann et al 2014 ; Rolf et al 2014 ). Hence, there is also much potential for strong selection at the VDR locus.…”
Section: Discussionmentioning
confidence: 99%
“…Besides numerous observations emphasizing the regulation of calcium/phosphate homeostasis, the involvement of vitamin D status in immune response is widely evident. Furthermore, HIV+ subjects with vitamin D receptor variants showed a significantly increased risk of progression to AIDS [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported results regarding the potential effects of VDRG polymorphisms on HIV infection, pathogenesis, and treatment outcome. VDR diplotypes in 5 untranslated region (UTR) and 3 UTR locus combinations were associated with the pathogenesis of AIDS [154]. The VDR variant rs1544410_AA was also associated with the progression to AIDS and resistance to HIV-1 [155].…”
Section: Effect Of Vdrg Polymorphisms On Hiv Infection and Pathogenesismentioning
confidence: 99%